Mathematics
tenneshiadodson
44

the work of a student to solve a set of equations is shown: equation a: y = 4 – 2z equation b: 6y = 2 – 4z step 1: –6(y) = –6(4 – 2z) [equation a is multiplied by –6.] 6y = 2 – 4z [equation b] step 2: 6y = 4 – 2z [equation a in step 1 is simplified.] 6y = 2 – 4z [equation b] step 3: 0 = 6 – 6z [equations in step 2 are added.] step 4: 6z = 6 step 5: z = 1 in which step did the student first make an error? step 4 step 3 step 2 step 1

+4
(1) Answers
KatriceLaigo

That would be step 2. step 1 is correct....multiplying the first equation by -6 which gives you : -6y = -24 + 12z but in step 2, the simplifying would be : y = 4 - 2z

Add answer